Formation of the Future Teacher’s Readiness to Professional Activity in the Dual-Oriented Education Conditions - Elmira, Aitenova; Laura, Shalabayeva; Tursynay, Abdykadyrova; Zhazira, Abdualieva; Aigerim, Baikulova (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
The reorientation of society to the market relations was required major changes in the system of vocational education. When employment, the employer is interested not store of theoretical knowledge of graduates of higher and secondary special educational institutions, but their preparedness to fulfillment of professional activities in this area. In connection with these requirements of employers and society in our country, were started the implementation of dual system of education. There has developed the innovative labor market in Kazakhstan. And it is necessary to review the traditional approaches in system of vocational education. However, the educational institutions cannot to shift to the new goals of specialists training yet. "Duality" means "double unity, duality". Dual training, as showed the practice of European education system is the product of close cooperation between educational institutions and employers for successful professional and social adaptation of future specialists. Together with this, given manuscript demonstrates the necessity of dual oriented education in educational system of the Republic of Kazakhstan for enhancement the professional preparation of the specialists